Structural design analysis of sandwich panels under axial compression load: Utilization of geometry and material variations - Alifianto, Muhammad Daffa; Rohman, Hamdani Maftuh; Pratama, Anandito Adam; Istanto, Iwan; Prabowo, Aditya Rio; Melnyk, Oleksiy; Do, Quang Thang; Muttaqie, Teguh; Budiana, Eko Prasetya; Sohn, Jung Min; Wijaya, Rahman (Department of Naval Architecture - Diponegoro University, 2025)
This study aims to analyze the performance of sandwich cylindrical shell structures under axial compression load by varying the geometry and types of material. Numerical simulations were conducted using ABAQUS software, employing the finite element method (FEM) to evaluate von Mises stress, displacement, and energy absorption. The materials used include ASTM 1045, ASTM A36, and Mild Steel, with geometry designs varying across five different configurations. The simulation results indicate that the combination of material and geometry has a significant impact on the structural response of the sandwich cylindrical shell. ASTM 1045 exhibited the highest von Mises stress and displacement, indicating both high strength and substantial deformation, while Mild Steel demonstrated better elastic properties. Geometry 4 combined with ASTM 1045 proved to be the strongest configuration, while the combination of Geometry 1 and Mild Steel was the most elastic. This study contributes to the development of more efficient and impact-resistant ship structural designs.